Studi Perbandingan Efektivitas Program Kesejahteraan Sosial Di Indonesia Dan Singapura - Saragih, Yessi Juwita Lestari; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
Social welfare is an important aspect in ensuring a decent life and security for society. Each country has different approaches and strategies in effortsto improve social welfare. This research aims to compare the effectivenessof social welfare programs in Indonesia and Singapore through a literature review study. By identifying and analyzing various literature from scientific journals, books, government reports, and international publications, this research disseminates government policies and regulations, budget allocations, community participation, benefit distribution systems, social andeconomic impacts, as well as cultural and social factors that influence success. social welfare programs in both countries. The research results show that Singapore has a well- coordinated policy framework and adequatebudget allocation, which supports the effectiveness of its social welfare programs. In contrast, Indonesia faces challenges in terms of policy coordination and budget constraints, which hinder the success of social welfare programs. This research provides recommendations for Indonesia to improve coordination between programs, strengthen budget allocations,increase community participation, improve the benefit distribution system, and consider cultural factors in program implementation. For Singapore, thisresearch suggests continuing to maintain a strong policy framework, ensuring funding continuity, and strengthening private sector and community participation. This study provides valuable insights for policy makers in designing and implementing more effective and sustainable social welfare programs